PENGUJIAN PENGGUNAAN BIOCHAR BERBAHAN BAKU SISA POHON KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY PADA TANAH ULTISOL ASAL GALANG - Jusy Siboro (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
The rest of the oil palm plantations in large quantities, if not processed, can damage the environment. if used properly, it can be used as biochar, which functions to improve the soil. This study aims to determine the effect of testing the use of Biochar made from raw residual Palm Oil Trees for The Growth Of Palm Oil Seeds (Elaeis guenensis Jacq.) in the Main Nursery in Ultisol. The research was conducted using a complete randomized design (RAL) non factorial with 4 replications. The factors is biochar consisting of 5 treatments: B0 (Control); B1 (biochar of stem palm oil); B2 (biochar of palm oil fronds); B3 (biochar of empty fruit bunch compost); B4 (biochar of stem palm oil + fronds + oil empty fruit bunch compost). The parameters observed were plant height, diameter of the stem and number of leaves. The results showed that administration of biochar had no significant effect on increasing plant height, application of biochar also had no significant effect on increasing the diameter the stem, application of biochar had no significant effect on increasing the giving biochar had no number of leaves of oil palm seedlings.